Examining the bleeding incidences associated with targeted therapies used in metastatic renal cell carcinoma. (December 2017) - Crist, MacKenzie; Hansen, Elizabeth; Chablani, Lipika; Guancial, Elizabeth
Highlights: Targeted therapies are the mainstay of treatment in metastatic renal cell carcinoma, and these therapies can cause bleeding events. According to trials searched on PubMed/Medline bevacizumab had the highest reported all Grade bleeding events, and axitinib had the lowest reported all Grade bleeding events. "Serious bleeding adverse events" reported on ClinicalTrials.gov revealed the highest incidence with sunitinib and lowest incidence with axitinib. Abstract: A systematic review was conducted to illustrate the bleeding risks associated with targeted therapies used in the treatment of metastatic renal cell carcinoma (mRCC). Eligible studies included phase II, III, or IV clinical trials using pazopanib, sunitinib, cabozantinib, lenvatinib, everolimus, temsirolimus, bevacizumab, axitinib, and/or sorafenib in the setting of mRCC. Types of bleeding event(s), bleeding event frequency, and incidence of thrombocytopenia were collected from the relevant articles. ClinicalTrials.gov was also searched for incidence of "Serious bleeding adverse effects" reported in these trials. The incidences of bleeding events ranged from 1 to 36%, and incidences of thrombocytopenia ranged from 2 to 78%. Available serious bleeding adverse events ranged from 1 to 7%. The highest percentage of bleeding incidences were seen with bevacizumab, while the lowest percentage of bleeding incidences were seen with axitinib. All of the included trials were of high quality per Jadad scoring.